Genetic hierarchy and temporal variegation in the clonal history of acute myeloid leukaemia - Pierre Hirsch (Nature Portfolio, 2016)
Pre-leukaemic clones, together with the propensity to cause disease in mice, are characterized by appearing early in myeloid leukaemia and being found at relapse. Here, the authors identify clones in human samples and find that they are characterized by hierarchically organized genetic lesions, which can be used to track evolution of the disease.